2016
DOI: 10.3109/0284186x.2015.1114672
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cancer of the head and neck in the elderly in Denmark, 1980–2012

Abstract: Background Squamous cell carcinoma of the head and neck (HNSCC) comprises a variety of malignant tumors. Due to the rarity of each individual malignant entity, knowledge of epidemiological changes and trends over time may be derived from data compiled in regional and national registries. This study analyzed the development in incidence rates and mortality in elderly HNSCC patients in Denmark between 1980 and 2012 with specific attention to compliance to radiotherapy, the main treatment modality of HNSCC in Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In elderly patients, HNSCC are rare [ 9 ]. Less than 20% of HNSCC patients get diagnosed at the age of >70 years [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly patients, HNSCC are rare [ 9 ]. Less than 20% of HNSCC patients get diagnosed at the age of >70 years [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients, HNSCC are rare [ 9 ]. Less than 20% of HNSCC patients get diagnosed at the age of >70 years [ 9 ]. At the same time, regarding the general increase in life expectancy, the proportion of elderly patients with HNSCC is expected to grow rapidly [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Danish study showed an increase in OCC incidence in men and a stabilization among women for all age groups from 1980 to 2012. For both sexes, incidence rates were the highest in the population aged 70 years or more [23]. The Dutch national incidence data (https://iknl.nl/nkr-cijfers (accessed on 1 October 2021)) also show an increase for both sexes (age groups 70-74, 75-79, 80-84, and >85 years).…”
Section: Incidence Of Oral Cavity Cancers Worldwidementioning
confidence: 99%
“…Recent literature regarding this matter has mainly focused on the incidence surge among young subjects (<45 years) worldwide, but also in France, and seems to imply the involvement of unknown RF [20,21]. However, American and European studies also suggested a trend for a rising incidence among elderly subjects, with a limited association with smoking and alcohol abuse [11,22,23].…”
Section: Incidence Of Oral Cavity Cancers Worldwidementioning
confidence: 99%